Group bargaining and conflict - Nicolas Quérou (Fondazione Eni Enrico Mattei (FEEM), 2010)
We consider a situation where groups negotiate over the allocation of a surplus (which is used to fund group specific goods). Each group is composed of agents who have differing valuations for public goods. Members choose a representative to take decisions on their behalf. Specifically, representatives can decide to enter either a (cooperative) negotiation protocol or a conflict to appropriate the surplus. In the cooperative negotiations, disagreement corresponds to a pro rata allocation (as a function of the size of the groups). We analyse the conditions (on the internal composition of the groups) under which conflict will be preferred to negotiated agreements (and vice versa), and we derive welfare implications. Finally, we provide results of comparative statics that highlight the influence of changes in the internal composition of groups and in their relative size on the profitability of negotiated agreements.
Keywords: C78; D74; J52; 330; Bargaining; Conflict; Agency Problem